Teologi Eksklusif Era Kolonial - Potret Pemikiran KH. Ahmad Rifa’i tentang Konsep Iman - Ma'mun Ma'mun (UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
This article will address interesting facts about the exclusivity of theology which appeared in the thoughts of KH. Ahmad Rifa’i (Batang) in the colonial era. The study will focus on the concept of faith initiated by Kiai Rifa'i in his works. Data was obtained from the works of Kiai Rifa'i who taught the students. These data will be analyzed by a phenomenological approach with reference to the theological and philosophical facts that characterize the thoughts of Kiai Rifa’i. The results of the study indicate that the theological exclusivity in the thinking of Kiai Rifa'i was formed because of the polarization of the quality of human faith is divided into three: (1) Iman Maqbul, is the faith of believers who only commit minor sins; (2) Iman Mauqūf, is the faith of those who commit the great sin of the wicked causes; (3) Iman Mardūd, the faith of the hypocrites and those who commit the great sins of the infidelity causes. From the trilogy of faith, several issues of fiqh are often punished by Kiai Rifa'i with exclusive conclusions such as in marriages and Friday Prayers (Shalat Jum’at) which according to him are punished illegally, because in those two problems there is the role of people whose quality of faith falls into the category of Mauquf Faith, namely the princes of marriage who want to help the colonial government (Netherlands).